Application of Adaptive Media and Enganging E-learning for Students in E-learning Courses - Ambiyar, Ambiyar; Verawardina, Unung; Lubis, Arina Luthfini; Ramadhani, Dochi; Wakhinuddin, Wakhinuddin; Asnur, Lise (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to apply adaptive and engaging e-learning media for students who take e-learning courses, and see how the results of learning styles and learning activities while using these media in the learning process. The research method used was an experiment. The instrument uses a learning style questionnaire and an observation sheet of e-learning activities. The findings in the experimental class students have varied learning styles such as visual, auditory and kinesthetic learning styles, from these results the kinesthetic learning styles are classified as higher, and the results of learning activities with a percentage of 73.75% are good categories. The results of the learning activities of the control class students with a percentage of 63.28% both categories. In conclusion, students use adaptive media egangging e-learning where the kinesthetic learning style is more domainic, and the results of student learning activities are higher than the results of activities using conventional e-learning media. The renewal of these findings contributes differently to previous online learning, because through adaptive and engaging e-learning media students are able to learn online according to their learning styles such as visual, kinesthetic and auditory learning styles on the website and accompanied by online learning activities.